2020
DOI: 10.7717/peerj.10107
|View full text |Cite
|
Sign up to set email alerts
|

Integrated network pharmacology and molecular docking approaches to reveal the synergistic mechanism of multiple components in Venenum Bufonis for ameliorating heart failure

Abstract: Venenum Bufonis (VB), also called Chan Su in China, has been extensively used as a traditional Chinese medicine (TCM) for treating heart failure (HF) since ancient time. However, the active components and the potential anti-HF mechanism of VB remain unclear. In the current study, the major absorbed components and metabolites of VB after oral administration in rats were first collected from literatures. A total of 17 prototypes and 25 metabolites were gathered. Next, a feasible network-based pharmacological app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…It is reported that these differential genes play an important role in the process of mitochondrial damage. [34][35][36][37][38][39] For example, the expression of ndufb6 and ndufs3 increased after AF-HF001 treatment, which increased myocardial contractility and improved oxidative damage. 38 Overexpression of Uqcrh can improve mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that these differential genes play an important role in the process of mitochondrial damage. [34][35][36][37][38][39] For example, the expression of ndufb6 and ndufs3 increased after AF-HF001 treatment, which increased myocardial contractility and improved oxidative damage. 38 Overexpression of Uqcrh can improve mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding PDB ID of the core targets was found in the PBD ( ) database and saved as pdb format. Then the target was dehydrated and hydrogenated to optimize ligand in Pymol ( Ren et al, 2020 ). Finally, the molecular docking was performed by AutoDock software to calculate the binding ability of the main active components of the Danshen-Guizhi drug pair to the core targets.…”
Section: Methodsmentioning
confidence: 99%
“…Ren et al [ 41 ] revealed the synergistic mechanism of multiple components in Venenum Bufonis for ameliorating heart failure by integrating network pharmacology and molecular docking approaches. Their study identified four key targets (ATP1A1, GNAS, MAPK1 and PRKCA) and three potential active leading compounds (bufotalin, cinobufaginol and 19-oxy-bufalin) that may play a key role in myocardial contraction.…”
Section: Pharmacological Activities Of Bufadienolidesmentioning
confidence: 99%